New guaiane-type sesquiterpenoid dimers from Artemisia atrovirens and their antihepatoma activity - Su, Lihua; Zhang, Xintian; Ma, Yunbao; Geng, Changan; Huang, Xiaoyan; Hu, Jing; Li, Tianze; Tang, Shuang; Shen, Cheng; Gao, Zhen; Zhang, Xuemei; Chen, Ji-Jun (Acta pharmaceutica Sinica. B, 2021)
Leading by cytotoxicity against HepG2 cells, bioactivity-guided fractionation of the EtOAc fraction from Artemisia atrovirens led to the isolation of 18 new guaianolide dimers, artematrolides A–R and lavandiolides A, B, C, H, and J. Eight compounds (1, 4, 10, 12, 13, and 19–21) were unambiguously confirmed by the single-crystal X-ray diffraction analyses, and the others were elucidated based on IR, UV, HRESIMS, 1D and 2D NMR experiments, and comparison of the experimental and calculated ECD data. Structurally, all of them were [4 + 2] Diels–Alder adducts of two monomeric guaianolides. The isolates were evaluated for their cytotoxicity against three human hepatoma cell lines, and 19 compounds demonstrated cytotoxicity against HepG2, SMMC-7721, and Huh7 cell lines. Especially, compounds 1, 12, 14, and 15 exhibited cytotoxicity with IC50 values of 4.4, 3.8, 7.6, and 6.7 μmol/L (HepG2), 9.6, 4.6, 6.6, and 6.0 μmol/L (SMMC-7721), and 7.6, 4.5, 6.9, and 5.6 μmol/L (Huh7), respectively. Notably, compound 12 showed the most promising activity against three human hepatoma cell lines and dose-dependently inhibited cell migration and invasion, induced G2/M cell cycle arrest and cell apoptosis in HepG2 cells, down-regulated the expression of BCL-2 and PARP-1, and activated PARP-1 to up-regulate the expression of cleaved-PARP-1. Twenty-three guaianolide dimers were isolated from Artemisia atrovirens. Nineteen compounds demonstrated cytotoxicity against HepG2, SMMC-7721, and Huh7 cell lines. The mechanism of the most active compound 12 was investigated. [Display omitted]